(untitled) (diségno, 2022)
“It is interesting to think about the relationship between drawing and design, and about the role of drawing in design: this is almost a play on words, but –as often happens– playing can lead us to reflect more deeply. On English-language design courses, the word ‘design’ is almost always accompanied by another term to specify the field in question: furniture design, car design, lighting design, and so forth. It is perhaps not very well-known, however; that the word ‘design’ actually derives from the Italian word ‘disegno’, meaning ‘drawing’, which in turn derives from the Latin ‘design-are’” [Pasca 2010, p. 12]. With this introduction, in the essay Drawing and Design, Vanni Pasca in 2010 questioned the positioning of sketching and, more generally, analog drawing as a suitable practice for transmitting a conceptual reflection irreplaceable of project: the manifestation of the idea. [read more]